Postmodernism: aesthetics and the art of virtuality - R. M. Rusin (Ukrainian Cultural Studies, 2019)
At the end of the 20 and the beginning of the 21 century as a result of the changes that took place in art, there was a need for a theoretical re- thinking of artistic practices. This task was assumed by artists, art critics, art critics and other agents of the artistic world, trying to clarify the possibility of a new vision of art, give it an objective assessment. Obviously, understanding the specifics of contemporary art is not so much in the assessment itself, but in clarifying the fundamentals of a different understanding of such concepts as "classical art", "contemporary art," "virtual art." If classical art received a thorough understanding of the history of art, art history and aesthetics for centuries, virtual art, as a specific form of contemporary art, needs to be thoroughly investigated. Contemporary art is experiencing significant transformations in the context of post-industrial culture. Increasingly important are computational methods for the production of virtual artefacts. The report notes that contemporary virtual art is a new space dynamically captured by the postmodernist practices of contemporary art. In modern practices of postmodernism in the field of virtual art with the rapid development of computer technology sharply decreases the fate of human presence in the process of creativity. Machine modelling as a product of collective creativity allows you to create a new virtual image, regardless of its existence in the real world. In modern practices in the field of virtual art, the idea of artificial ("synthetic imagination") is used, which is a machine imagination with the use of artificial modelling of man’s imagination. Artificial imagination with the help of interactive search allows you to synthesize images from the data- base and create a new virtual image, regardless of its existence in the real world. Thus, the rapid development of computer technology is increasingly reducing the fate of human presence in the field of virtual art. Postmodern experiments stimulate the erosion of the boundaries between traditional forms and genres of art. The perfection and availability of technical means of production, the development of computer technology practically led to the disappearance of original creativity as an act of individual creation.